2001
DOI: 10.1046/j.1365-2044.2001.01763-3.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose intrathecal diamorphine for analgesia after Caesarean section

Abstract: SummaryAcute Physiology and Chronic Health Evaluation (APACHE) II scoring is widely used as an index of illness severity, for outcome prediction, in research protocols and to assess intensive care unit performance and quality of care. Despite its widespread use, little is known about the reliability and validity of APACHE II scores generated in everyday clinical practice. We retrospectively re-assessed APACHE II scores from the charts of 186 randomly selected patients admitted to our medical and surgical inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Despite some minor patient dissatisfaction with spinal block, overall patient satisfaction was good in our study population. More than 70% of our patients had neuraxial anaesthesia, which included diamorphine to provide postoperative analgesia for up to 24 h. 18 Although patient satisfaction surveys can be useful, they may be subjective and depend on maternal recall. However, these elements in our survey were minimal, as our standardized report was promptly collected directly by an anaesthetist, but usually not the one who performed the anaesthesia; in order to further encourage truthful responses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some minor patient dissatisfaction with spinal block, overall patient satisfaction was good in our study population. More than 70% of our patients had neuraxial anaesthesia, which included diamorphine to provide postoperative analgesia for up to 24 h. 18 Although patient satisfaction surveys can be useful, they may be subjective and depend on maternal recall. However, these elements in our survey were minimal, as our standardized report was promptly collected directly by an anaesthetist, but usually not the one who performed the anaesthesia; in order to further encourage truthful responses.…”
Section: Discussionmentioning
confidence: 99%
“…We used postoperative opioid requirement as the primary outcome in keeping with previous dose-response studies. [5][6][7] It was anticipated that a single analysis of variance across all groups would be used to see whether any differences were present. Audit data from our unit indicated mean (SD) postoperative subcutaneous diamorphine requirements for the different doses of intrathecal diamorphine of 14.1 (7.3) mg for placebo, 12.5 (9.46) mg for 100 lg, 10.7 (8.7) mg for 200 lg and 8.7 (8.2) mg for 300 lg.…”
Section: Methodsmentioning
confidence: 99%
“…High-dose diclofenac (200 mg in 24 h) is opioid-sparing but without an increased incidence of side effects. 2,3 Intrathecal diamorphine is known to improve postoperative analgesia in this group of patients [4][5][6][7] and previous studies had indicated that approximately 300 lg was the optimal dose. Spinal opioids also have dose-dependent side effects of nausea, itching and respiratory depression.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a doubleblind study of primigravidae, epidural diamorphine has been found to effective for pain relief in labour [29]. Diamorphine has been used after Caesarean section for analgesia [30], and has been found to be safe in a double-blind study of patients undergoing Caesarean section with pain scores and other adverse effects reduced in a dose-dependent manner by intrathecal diamorphine [31]. It is an indication of the relaxed attitude of British physicians to diamorphine that it is also used with newborn infants and with children.…”
Section: Discussionmentioning
confidence: 99%